Coronavirus Geopolitics. A Reflection on the Russian Case - Carmen Scocozza (Culture e Studi del Sociale)
The current pandemic has shown that, over and above the more immediate consequences to be tackled, such as the health emergency and the economic crisis, there are long-term effects that will require reflection at a global level. In this article, we will analyse how the fight against coronavirus has become an interesting test of whether the Russian Government can enjoy comparative advantages over Western democracies. In particular, we highlight how the global health emergency is being used by the Kremlin to fuel the Russian narrative on an energetic and resolute country, against a divided and weakened West, and to loudly invoke a different world order where Moscow could find new centrality.